1992
DOI: 10.1128/aac.36.7.1382
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pharmacokinetic interaction between cefepime and amikacin in humans

Abstract: The interaction potential between cefepime and amikacin was investigated in a steady-state pharmacokinetic study in 16 healthy male subjects. Eight subjects (group A) received a first course of 2,000 mg of cefepime; this was followed by a second course of 2,000 mg of cefepime with 300 mg of amikacin and a third course of 2,000 mg of cefepime. Eight other subjects (group B) received a first course of 300 mg of amikacin, a second course of 300 mg of amikacin with 2,000 mg of cefepime, and a third course of 300 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…These results agree with those of other authors [3] and confirm the absence of significant pharmacokinetic interaction between cefepime and amikacin when co-administered in 16 individuals. The estimated pharmacokinetics for amikacin were similar to those already described (Table 1) whereas glomerular filtration was the main mechanism of excretion for both cefepime and amikacin as also noted in the present study.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results agree with those of other authors [3] and confirm the absence of significant pharmacokinetic interaction between cefepime and amikacin when co-administered in 16 individuals. The estimated pharmacokinetics for amikacin were similar to those already described (Table 1) whereas glomerular filtration was the main mechanism of excretion for both cefepime and amikacin as also noted in the present study.…”
Section: Discussionsupporting
confidence: 95%
“…Patients with nosocomial infections are often given a variety of drugs thus raising the question of the existence of any interaction between co-administered ␀-lactams and amikacin. Although one previous study has shown the absence of any pharmacokinetic interaction between cefepime and amikacin [3], the present study aimed to investigate the pharmacokinetic parameters of ceftazidime, imipenem and aztreonam after their intravenous administration singly or in combination with amikacin in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the antibacterial efficacy is greatest with treatment regimens that result in the highest peak concentration in serum and largest area under the serum time-concentration curve [19]. There was no evidence of pharmacokinetic interaction be tween cefepime 2 g and amikacin 300 mg fol lowing concomitant intravenous administra tion of both drugs into contralateral forearm veins of healthy volunteers [20].…”
Section: Discussionmentioning
confidence: 93%
“…Data from the pharmacokinetic analysis are given in Table 1, except for amikacin plus cefepime because they do not affect the elimination of each other (2).…”
mentioning
confidence: 99%
“…The coefficient of variability was Յ5% for each antibiotic assay. The pharmacokinetic values half-life (T 1/2 ), peak concentration (C max ), first occurrence of C max (T max ), area under the concentration-time curve extrapolated to infinity (AUC), and area under the concentration-time curve from 0 to 24 h (AUC 0-24 ) were calculated by a noncompartmental method (2).…”
mentioning
confidence: 99%